WHITHOUT BOURDER, WITHOUT _CUARTEL_. THE ANARCOCOMUNIST OF PLM, 1900-1930 (Tzintzun, Revista de Estudios Históricos, 2016)
The Liberal Mexican Party (PLM) was an organization which at the beginningadopted radical, liberal ideas, but later it became anarchist – communist. Itspreeminence took place between 1900 and 1930, at the same time that many importantsocieties lived similar problems caused by the radicalism. The article emphasizes therelations the PLM had with other countries beyond the border. It analyzes how notonly did the “magonistas” (Ricardo Flores Magón’s supporters) know aboutpoliticians and political dynamics in the United States and Mexico, but they alsoknew that any transformation of the society in Mexico depended on the changes inthe USA. Furthermore, this transformation should be worldwide, a world socialrevolution that ought to be actively driven by individuals. That is why they plannedto become activists beyond the borders, this is internationally.
Keywords: The Liberal Mexican Party; anarcocomunist; magonismo; transnational activist